The effect of Constructive Conflict on the Organizational Identification Applied Research in the Ministry of Planning - سلمان فاضل حمد; صالح خالد مهدي (Journal of Economics and Administrative Sciences, 2015)
This research deals with the effect of constructive conflict of the organizational identification .These relatively recent subjects have relative importance in the field of administration and they have strong effect in the success of organizations .The objective of this research is to detect the level of the constructive conflict and the organizational identification in the center of The Ministry of Planning. So, two major hypotheses were formulated The first are searched the correlation between the constructive conflict and the organizational identification and it emerged with four sub-hypotheses searched the correlation among every dimension of the constructive conflict with the organizational identification .The second major hypothesis searched the effect of constructive conflict on the organizational identification and it emerged with four sub-hypotheses searched the effect of every dimension of constructive conflict on the organizational identification. Several statistical methods have been used in this research such as the Mean, the Spearman correlation, the simple linear regression, and the multiple linear regression .This research is applied on the random sample in the center of the ministry of planning. The number of individuals of this sample was (83). The information is collected by questionnaires and personal interviews. The research reached to a set of conclusions. The most important is that there is a correlation between the constructive conflict and the organizational identification. Moreover, there is an effect of constructive conflict on the organizational identification. The research has concluded that the constructive conflict and the organizational identification have not been at the required level. Also, there is no strong correlation and strong effect of constructive conflict on the organizational identification. The research ends with a set of recommendations, the most important is the necessity to educate employees in this ministry about the positive effects of the constructive conflict and its role to create a climate of cooperation and trust among the employees and its role to improve performance in this ministry and the necessity of keeping away from (win – lose) logic in the conflict. The ministry must also mind and maintain the positive relationship which link the employee with this ministry for this relationship contributes to increase the motivation and the desire to stay to work in the ministry and its effect on the performance and raise the efficiency of the employees